Reducing the internet traffic in IoT-based monitoring and control system through a combination of WSN and LoRaWAN networks. (16th March 2022) - Bhavatharangini, S.; Ramakrishnan, Sabitha
LoRa is a wireless communication technology with long transmission distance, low power consumption, low transmission speed, low complexity and low cost. Through the comparison and analysis of several wireless communication technologies, a temperature monitoring platform based on LoRa spread spectrum and wireless sensors is proposed. Thus a low-cost and battery-supplied wireless sensor network (WSN) for fine-grained, flexible and data centric temperature monitoring system is proposed. The proposed system uses localised LoRa-based communication among the nodes of a wireless sensor network and IoT-based monitoring and control through a single LoRaWAN gateway. Thus, the proposed system offers several advantages over a conventional IoT-based monitoring and control system, namely: 1) reduced internet traffic; 2) low-cost end devices with simple LoRa transceivers and a single coordinator per cluster with LoRaWAN gateway; 3) remote monitoring and control of end devices through the gateway.